Quercetin improved histological structure and upregulated adiponectin and adiponectin receptors in the placenta of rats with gestational diabetes mellitus. (March 2021) - Mahabady, Mahmood Khaksary; Shamsi, Mohammad Mehdi; Ranjbar, Reza; Tabandeh, Mohammad Reza; Khazaeel, Kaveh
Abstract: Introduction: Gestational diabetes mellitus (GDM) is a metabolic syndrome among pregnant mothers that increases the risk of developing growth disorders in the fetus and the placenta. Adiponectin is an adipokine, which plays a central role in the regulation of glucose and lipid metabolism, energy homeostasis, and insulin resistance in various tissues. Quercetin is a natural flavonoid with beneficial effects in the diabetic animal model, but data related to its effect on histological change and adiponectin system in the placenta of GDM are limited. In the current study, some histological changes and expression of adiponectin and its two receptors in the placenta of rats with GDM were investigated. Methods: This study was carried out on placentas from the rodent model. To induce GDM, female rats were treated with a single dose of STZ. Placenta tissue was harvested and stained by PAS method. Protein and mRNA levels of adiponectin and its two receptors were assessed by immunohistochemistry and Real time PCR analysis, respectively. Results: The results showed the increased number of glycogen cells and thickness of the labyrinth interhemal membrane (LIM) in the embryonic part of the placenta in diabetic rats, while the use of quercetin significantly prevented their increase in diabetic rats. Treatment of the diabetic group with quercetin caused significantly increased adiponectin expression and decreased its receptors.The immunohistochemical study revealed the expression of AdipoR2 in the cytoplasm of syncytiotrophoblast and cytotrophoblast cells. Discussion: The results indicated that quercetin in pregnant diabetic rats could attenuate the histological abnormalities and improved adiponectin system dysregulation in the placenta. Highlights: STZ-induced diabetes resulted increased number of glycogen cells (GCS ) and thickness of the labyrinth interhemal membrane in from embryonic part of the placenta in diabetic rats. In the diabetic rats, the expression level of adiponectin in the placenta was significantly decreased compared to the control group. Immunohistochemical analysis showed that Adipo-R2 was mainly expressed in the cytoplasm of cytotrophoblasts and syncytiotrophoblasts. In the diabetic group treated with quercetin compared to the untreated diabetic group the expression of both receptors were decreased, but their expression did not return to the normal level.